Kualitas Pelayanan Administrasi Pasien Di Puskesmas Singgani Kota Palu - Rahman, Fathur; Maryam, Sinta; Agil, Muhammad; Desy, Desy; Adji, Vita Adonia; Mustainah, Mustainah; Kurnia, Intam; Haryono, Dandan; Borman, Mohammad Riski (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2025)
This study aims to analyze the quality of patient administration services at Singgani Health Center in Palu City using the five dimensions of SERVQUAL approach (tangibles, reliability, responsiveness, assurance, and empathy). Health centers as primary health care facilities require optimal administrative systems to support smooth health service delivery to the community. This research employs a descriptive qualitative method with data collection techniques through in-depth interviews, observation, and documentation. Research informants consisted of administrative staff, head of administration, and patients selected through purposive sampling. Data analysis used the Miles and Huberman model including data reduction, data presentation, and conclusion drawing. The results showed that the quality of administrative services has generally been running well with the dimensions of reliability, responsiveness, assurance, and empathy showing positive performance. Administrative staff were assessed as responsive, friendly, meticulous in recording, and able to provide special attention to patients. However, the tangibles dimension still requires improvement, especially regarding the comfort of the waiting room during increased patient volumes. This study recommends optimization of physical infrastructure, enhancement of human resource capacity, development of queue management systems, and strengthening of periodic service monitoring and evaluation